(untitled) (Bangladesh Medical Journal, 2020)
Chronic kidney disease (CKD) has become a global public health concern. The adverse outcome of CKD are high in number in developing countries due to scarcity of facilities for renal replacement therapy and high cost of services for management of ESRD. It is one of the leading cause of hospital deaths. CKD is strongly associated with diabetes, hypertension, glomerulonephritis and elevated lipids. Therefore, identifying the preventable risk factors, pathophysiological mechanisms and stratification of CKD helps in decreasing and slowing its progression. This study was conducted for the staging of chronic kidney disease (CKD) and assessment of the risk factors with CKD in hospitalized patients of Dhaka Medical College Hospital in collaboration with Medicine and Nephrology department. This was a cross sectional observational study where 125 patients having chronic kidney diseases (CKD) were diagnosed on the basis of history, clinical examinations and investigations, who had fulfill the inclusion and exclusion criteria admitted in the department of medicine and department of nephrology from January to December 2016. Sampling method was purposive sampling. A specifically designed questionnaire were used to get the personal and medical history data. Blood and urine samples were collected and data was analyzed using SPSS (22.00). Out of 125 patients, no Stage-1 patient was found, remaining were Stage- 2 CKD 7.2%, Stage- 3 CKD 63.2%, Stage- 4 CKD was 25.6%, and Stage- 5 CKD was 4%. Among 125 participants, 52.0% had glomerulonephritis (GN), 31.2% had diabetes mellitus (DM) and 9.6% had hypertension (HTN). Mean age was 48.41 (±13.99) years, mean body weight was 50.61 (±10.73) Kg, mean BMI was 22.9 (±1.69), male female ratio was 3.6:1. Age group 51 to 60 years were suffering more. The association between CKD and other risk factors including obesity and overweight, use of tobacco, diabetes and hypertension were highly significant. The commonest risk factors for CKD like DM and HTN are also alarmingly high and obviously adding to the existing burden of CKD. Early detection of the risk factors of CKD, early referral to nephrologist, appropriate treatment of hypertension, DM, GN and other risk factors, life style modification with specific emphasis on reduction in salt intake, physical exercise, and abstinence from smoking would retard progression of kidney disease to an advanced stage. Bangladesh Med J. 2020 May; 49(2) : 19-24